Robust historical timber inventories describe patterns of forest structure, composition, and competition across a wide latitudinal gradient - Jessika R. McFarland; Eve Ryan; Brandon M. Collins; R. Keala Hagmann; Robert A. York; Scott L. Stephens (Forest Ecology and Management, 2026)

Comparing species richness estimators for nested and sequential sampling designs: contrasting Bayesian hierarchical models against conventional estimators - Timothy R. Toavs; Pedro Peres-Neto; Julian D. Olden; Brandon K. Peoples; Stephen R. Midway (Community Ecology, 2026)
Assessing species richness (i.e., the number of species in a specific area) is of significant ecological relevance across theoretical, empirical, and practical applications. Accurately estimating species richness remains a persistent statistical challenge, as direct species counts are often unreliable. Consequently, numerous species richness estimation methods have been developed to accommodate a wide range of data types, research goals, assumptions, and sampling designs. The advent of extensive ecological databases and advanced computational capabilities has created new opportunities to apply sequential sampling designs, such as (hierarchically) nested approaches, for more accurate species richness estimation by recording the presence or absence of species over time and space (i.e., across multiple communities or sampling areas). We propose leveraging large-scale datasets by incorporating random effects into non-linear asymptotic functions. In this framework, species richness is treated as a random variable drawn from an estimable distribution. Specifically, we introduce Bayesian hierarchical models in this framework to estimate species richness. We compare our proposed Bayesian models to traditional estimators through simulations and an empirical example of stream fish communities, hierarchically nested within watersheds at the continental scale. The conventional Chao2 performed best, but our findings indicate that Bayesian hierarchical models provide species richness estimates that are comparable in bias and accuracy to traditional estimators, while offering greater precision. However, this gain in precision may come with trade-offs, such as sensitivity to model assumptions or potential biases in certain scenarios.

Cumulative effects of forest fuel reduction and restoration treatment regimes on horizontal and vertical structure in the Sierra Nevada - Sean P. Reilly; Brandon M. Collins; John J. Battles; Rob A. York; Scott L. Stephens (Forest Ecology and Management, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Urban greening and water strategies are key to adapt Australian cities to climate change and urban growth - Valentina Marchionni; Christopher Szota; Claire Farrell; Stephen J. Livesley; Kerry A. Nice; Veljko Prodanovic; Sally Thompson; Pui Kwan Cheung; Hamideh Nouri; Mathew Lipson; Brandon Winfrey (Journal of Hydrology, 2026)

Finding floral and faunal species richness optima among active fire regimes - Zachary L. Steel; Alissa M. Fogg; Raphaela Floreani Buzbee; Kate Wilkin; Brandon M. Collins; Ryan Burnett; Marc D. Meyer; Amarina Wuenschel; Scott L. Stephens (Conservation Biology, 2025)
Changing fire regimes have important implications for biodiversity and challenge traditional conservation approaches that rely on historical conditions as proxies for ecological integrity. This historical‐centric approach becomes increasingly tenuous under climate change, necessitating direct tests of environmental impacts on biodiversity. At the same time, widespread departures from historical fire regimes have limited the ability to sample diverse fire histories. We examined 2 areas in California's Sierra Nevada (USA) with active fire regimes to study the responses of bird, plant, and bat communities to a broad spectrum of temporal, spatial, and severity patterns of fire. Bird and plant species richness peaked in the first decade following fire. Species richness was highest with moderate burn severity for birds and with low burn severity for plants. Bat richness increased with longer mean fire‐return intervals and was greatest in landscapes that included predominantly unburned areas or moderate to high burn severity patches. All taxa responded positively to pyrodiversity, with effect sizes varying with the metric used to assess variation in fire patterns. Our results suggest that restoring historical fire regimes would benefit biodiversity relative to most contemporary dry forests in California, but that total species richness would be highest under somewhat more frequent and varied severity fires than historical targets would indicate. Given the variable optima among taxa, managing for a range of complementary conditions that create local and landscape heterogeneity would best accommodate diverse flora and fauna and other forest conservation objectives.

Submovements Derived from Wearable Sensors Capture Ataxia Severity and Differ Across Motor Tasks and Directions of Motion - Siddharth Patel; Brandon Oubre; Christopher D. Stephen; Jeremy D. Schmahmann; Anoopum S. Gupta (The Cerebellum, 2025)

Nitrogen fixation in Pampinifervens, a new species-rich genus of Aquificaceae that inhabits a wide pH range in terrestrial hot springs - Marike Palmer; Nancy O. Nou; Lara A. Turello; Carolyn E. Power; John C. Ong; Jonathan K. Covington; Dengxun Lai; Xavier Mayali; Anna-Louise Reysenbach; Yan-Ling Qi; Jeremy A. Dodsworth; Jian-Yu Jiao; et al. (Systematic and Applied Microbiology, 2025)

Mapping Oak (Quercus spp.) Regeneration Potential Within the Nantahala National Forest - Quentin Ikuta; John Zobel; Joseph Knight; Jonathan Knott; Brandon Stephens; Nicholas J. Partington; Marcella A. Windmuller-Campione (Journal of Forestry, 2025)
Forest mesophication threatens the regeneration and potential future perpetuation of oak ( Quercus spp.) forests throughout southern Appalachia and eastern United States (US). We explored methods to produce stand-scale oak site suitability maps, within the Nantahala National Forest in North Carolina, which can be used to prioritize site-specific treatments to allow for oak regeneration and recruitment using silvicultural strategies to reduce forest mesophication. To establish initial conditions, USDA Forest Service common stand exam quick plot protocol was followed, and plot data collected from June through August 2023 at 180 sample points within 15 stands totaling 500 acres. Collection of seedling height class data was important for showing a gap in regeneration, between the number of small seedlings (~ 1 ft) (1038 stems) and large seedlings (> 4.5 ft) (301 stems). Two popular site suitability modeling techniques, Maximum Entropy (MaxEnt) and Random Forest, were run for five common oak species with seven predictor variables including available water capacity, elevation, eastness, ecozone, northness, soil acidity, and soil type. MaxEnt models consistently outperformed Random Forest models with the most important variables including ecozone, soil acidity, and soil type. The maps highlight locations that can be prioritized for silvicultural treatments that target regeneration and recruitment of oaks to combat or reverse forest mesophication.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Extreme Weather Magnifies the Effects of Forest Structure on Wildfire, Driving Increased Severity in Industrial Forests - Jacob I. Levine; Brandon M. Collins; Michelle Coppoletta; Scott L. Stephens (Global Change Biology, 2025)
Despite widespread concern over increases in wildfire severity, the mechanisms underlying this trend remain unclear, hampering our ability to mitigate the severity of future fires. There is substantial uncertainty regarding the relative roles of extreme weather conditions, which are exacerbated by climate change, and forest management, in particular differences between private industrial timber companies and public land agencies. To investigate the effects of extreme weather and forest management on fire severity, we used light detection and ranging (LiDAR) data to characterize pre‐fire forest structure across five large wildfires which burned 460,000 ha in the northern Sierra Nevada, California, USA. We found that the odds of high severity fire occurrence in these fires were 1.45 times higher on private industrial land than in publicly owned forests, an effect equivalent to a three standard deviation decrease in fuel moisture. Next, we quantified the relationships between key forest structure metrics and the probability of high severity fire, as well as how these relationships were modified by extreme weather. We found that dense, spatially homogeneous forests with high ladder fuels were more likely to burn at high severity. Extreme weather magnified the effect of density, suggesting that treatments which remove overstory trees are especially important in extreme conditions. Forests managed by private industry were more likely to be dense, spatially homogeneous, and contain high ladder fuel loads than publicly owned forests, offering a potential explanation for the increase in high‐severity fire occurrence on private industrial land. Overall, these results illustrate the need for comprehensive forest management to mitigate fire severity in a warmer future.

Nonnative Species Richness and Dominance Reveal Differing Support for Invasion Theory at a Continental Extent - Lily M. Thompson; William K. Annis; Stephen R. Midway; Julian D. Olden; Brandon K. Peoples (Global Ecology and Biogeography, 2025)
Aim Empirical tests of conceptual hypotheses describing species invasions often differ depending on the spatial scale (spatial resolution and extent of study area) at which they were conducted. Some of this disparity may arise from tradeoffs in data quality necessitating the use of different indices of community invadedness among scales. Local‐scale studies typically use fine‐resolution, descriptive measures of community invadedness (‘dominance’, the proportion nonnative individuals) at limited spatial extents, while macroscale studies often aggregate datasets to cover large spatial extents but use coarser spatial resolution and less descriptive indices (nonnative species richness). We investigated the consequences of using different indices to represent community invadedness at different spatial scales, and explored the implications for hypothesis testing when nonnative richness and dominance are not related. Location 23,793 stream segments within 17 regional watersheds, conterminous United States. Time Period 2000–2023. Major Taxa Studied Freshwater fishes. Methods Using a large‐extent, fine‐resolution dataset, we evaluated the correlation between nonnative species richness and dominance in communities, and compared empirical support for prominent invasion hypotheses (biotic resistance, disturbance facilitation) in identical Bayesian hierarchical models with community invadedness represented by each metric. Results Nonnative richness and dominance were weakly correlated, allowing us to classify communities into four archetypes based on relationships between the two indices. Empirical support for both invasion hypotheses differed between the two indices of community invadedness both overall and within regional watersheds. Main Conclusions Nonnative species richness and dominance describe different facets of the invasion process and may under‐ or over‐represent community invadedness when considered alone. Empirical disparity between models estimating the two metrics may be an important source of scale‐dependent inference in invasion ecology. When assembling datasets for macroscale studies, retaining fine spatial resolution as much as possible will allow researchers opportunities to use more descriptive and potentially complementary indices of community invadedness.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Subcellular localization of SARS-CoV-2 E and 3a proteins along the secretory pathway - Joshua J. Hinkle; Kathleen A. Trychta; Emily S. Wires; Raven M. Osborn; Justin R. Leach; Zoha F. Faraz; Reinis Svarcbahs; Christopher T. Richie; Stephen Dewhurst; Brandon K. Harvey (Journal of Molecular Histology, 2025)
SARS-CoV-2 E and 3a proteins are important for the assembly, budding, and release of viral particles. These two transmembrane proteins have been implicated in forming channels in the membrane that allow the transport of ions to favor viral replication. During an active infection, both proteins generally localize to the endoplasmic reticulum (ER), ER-Golgi intermediate compartment (ERGIC), and the Golgi where viral assembly occurs. The ER and Golgi are critical for the proper packaging and trafficking of cellular proteins along the secretory pathways which determine a protein’s final destination inside or outside of the cell. The SARS-CoV-2 virus primarily infects epithelial cells that are highly secretory in nature such as those in the lung and gut. Here we quantified the distribution of SARS-CoV-2 E and 3a proteins along the secretory pathways in a human intestinal epithelial cell line. We used NaturePatternMatch to demonstrate that epitope-tagged E and 3a proteins expressed alone via transient transfection have a similar immunoreactivity pattern as E and 3a proteins expressed by wild-type viral infection. While E and 3a proteins localized with all selected cellular markers to varying degrees, 3a protein displayed a higher correlation coefficient with the Golgi, early/late endosome, lysosome, and plasma membrane when compared to E protein. This work is the first to provide quantification of the subcellular distribution of E and 3a proteins along the multiple components of the secretory pathway and serves as a basis to develop models for examining how E and 3a alter proteostasis within these structures and affect their function.

Determination of a plasma retinol reference interval in eastern collared lizards (Crotaphytus collaris) - Brandon J. Louth; Stephen A. Smith; McAllister Council-Troche (Journal of Exotic Pet Medicine, 2025)

Spatial Scale and the Underestimation of Stream Fish Community Invadedness - Lily M. Thompson; William K. Annis; Stephen R. Midway; Julian D. Olden; Brandon K. Peoples (Global Ecology and Biogeography, 2025)
Scale‐Dependency of Native Status Classifying populations as native or nonnative requires well‐defined range boundaries for species. While many studies define native status according to large biogeographic realms, natural dispersal barriers often limit species distributions at regional or smaller spatial extents. As such, native/nonnative definitions are inherently scale‐dependent and estimates of community invadedness thus depend on the spatial resolution at which native status is defined. For example, nonnative species can be introduced among realms, among regions within realms, and among ecological provinces within regions (hereafter, simply “provinces”). By explicitly considering the scale‐dependency of native/nonnative status definitions, we can more effectively compare results across studies, more comprehensively evaluate the degree of invasion levels, and more objectively communicate the native status of a species. Location 30,034 stream segments, conterminous United States. Time Period 2000–2023. Major Taxa Studied Freshwater fishes. Quantifying Fish Community Invadedness Across US Streams We illustrate the importance of scale‐dependent native status definitions by quantifying nonnative species richness and relative abundance in stream fish communities across the United States, finding that provincially nonnative species are nearly four times as prevalent as extra‐realm nonnative species, and represented approximately 10% of all individuals in average community surveys. Implications Unrealistically broad native status definitions underestimate community invadedness. Dismissing regionally and provincially nonnative species can have severe ecological consequences, including displacement and hybridisation with native species and the loss of unique communities through biotic homogenisation. These consequences may undermine efforts to maintain and protect distinct local biodiversity and conserve endemic species.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Early impacts of fire suppression in Jeffrey pine – Mixed conifer forests in the Sierra San Pedro Martir, Mexico - Scott L. Stephens; Christina Fossum; Brandon M. Collins; Hiram Rivera Huerta (Forest Ecology and Management, 2024)

A model for evaluation of sediment exposure and burial for freshwater mussels from heavy particle sedimentation - Binbin Wang; Brandon J. Sansom; Wenyu Zhu; James Kunz; M. Christopher Barnhart; Henry Brown; Stephen McMurray; Andrew D. Roberts; Christopher Shulse; Caleb J. Knerr; Kathleen Trauth; Jeffery A. Steevens; et al. (Ecological Modelling, 2024)

Microbial respiration in contrasting ocean provinces via high-frequency optode assays - Melanie R. Cohn; Brandon M. Stephens; Meredith G. Meyer; Garrett Sharpe; Alexandria K. Niebergall; Jason R. Graff; Nicolas Cassar; Adrian Marchetti; Craig A. Carlson; Scott M. Gifford (Frontiers in Marine Science, 2024)
Microbial respiration is a critical component of the marine carbon cycle, determining the proportion of fixed carbon that is subject to remineralization as opposed to being available for export to the ocean depths. Despite its importance, methodological constraints have led to an inadequate understanding of this process, especially in low-activity oligotrophic and mesopelagic regions. Here, we quantify respiration rates as low as 0.2 µ mol O 2 L -1 d -1 in contrasting ocean productivity provinces using oxygen optode sensors to identify size-fractionated respiration trends. In the low productivity region of the North Pacific Ocean at Station Papa, surface whole water microbial respiration was relatively stable at 1.2 µ mol O 2 L -1 d -1 . Below the surface, there was a decoupling between respiration and bacterial production that coincided with increased phytodetritus and small phytoplankton. Size-fractionated analysis revealed that cells <5 µ m were responsible for the majority of the respiration in the Pacific, both at the surface and below the mixed layer. At the North Atlantic Porcupine Abyssal Plain, surface whole water microbial respiration was higher (1.7 µ mol O 2 L -1 d -1 ) than in the Pacific and decreased by 3-fold below the euphotic zone. The Atlantic size-fraction contributions to total respiration shifted on the order of days during the evolution of a phytoplankton bloom with regular storm disturbances. The high-resolution optode method used in the Atlantic captured these significant shifts and is consistent with coinciding stain-based respiration methods and historical site estimates. This study highlights the dynamic nature of respiration across vertical, temporal, and size-fractionated factors, emphasizing the need for sensitive, high-throughput techniques to better understand ocean ecosystem metabolism.

Trends in prescribed fire weather windows from 2000 to 2022 in California - Christina A. Fossum; Brandon M. Collins; Connor W. Stephens; Jamie M. Lydersen; Joe Restaino; Taj Katuna; Scott L. Stephens (Forest Ecology and Management, 2024)

Coyotes eat flies at carrion - David S. Mason; Abby K. Jones; Brandon T. Barton; Mike Proctor; Stephen L. Webb; Marcus A. Lashley (Food Webs, 2023)

Shifting taxonomic and functional community composition of rivers under land use change - Kai Chen; Stephen R. Midway; Brandon K. Peoples; Beixin Wang; Julian D. Olden (Ecology, 2023)
Land use intensification has led to conspicuous changes in plant and animal communities across the world. Shifts in trait‐based functional composition have recently been hypothesized to manifest at lower levels of environmental change when compared to species‐based taxonomic composition; however, little is known about the commonalities in these responses across taxonomic groups and geographic regions. We investigated this hypothesis by testing for taxonomic and geographic similarities in the composition of riverine fish and insect communities across gradients of land use in major hydrological regions of the conterminous United States. We analyzed an extensive data set representing 556 species and 33 functional trait modalities from 8023 fish communities and 1434 taxa and 50 trait modalities from 5197 aquatic insect communities. Our results demonstrate abrupt threshold changes in both taxonomic and functional community composition due to land use conversion. Functional composition consistently demonstrated lower land use threshold responses compared to taxonomic composition for both fish (urban p = 0.069; agriculture p = 0.029) and insect (urban p = 0.095; agriculture p = 0.043) communities according to gradient forest models. We found significantly lower thresholds for urban versus agricultural land use for fishes (taxonomic and functional p p = 0.001; functional p = 0.033). We further revealed that threshold responses in functional composition were more geographically consistent than for taxonomic composition to both urban and agricultural land use change. Traits contributing the most to overall functional composition change differed along urban and agricultural land gradients and conformed to predicted ecological mechanisms underpinning community change. This study points to reliable early‐warning thresholds that accurately forecast compositional shifts in riverine communities to land use conversion, and highlight the importance of considering trait‐based indicators of community change to inform large‐scale land use management strategies and policies.

Vegetation type change in California’s Northern Bay Area: A comparison of contemporary and historical aerial imagery - Hannah M. Fertel; Brandon M. Collins; Jamie M. Lydersen; Scott L. Stephens (Forest Ecology and Management, 2023)

Corrigendum to “Harmonization of acronyms for volatile organic compound metabolites using a standardized naming system” [Int. J. Hygiene Environ. Health 235 (2021) 113749] - Denise S. Tevis; Sharon R. Flores; Brandon M. Kenwood; Deepak Bhandari; Peyton Jacob; Jia Liu; Pawel K. Lorkiewicz; Daniel J. Conklin; Stephen S. Hecht; Maciej L. Goniewicz; Benjamin C. Blount; Víctor R. De Jesús (International Journal of Hygiene and Environmental Health, 2023)

Stable isotopes of nitrate record effects of the 2015–2016 El Niño and diatom iron limitation on nitrogen cycling in the eastern North Pacific Ocean - Margot E. White; Patrick A. Rafter; Brandon M. Stephens; Matthew R. Mazloff; Scott D. Wankel; Lihini I. Aluwihare (Limnology and Oceanography, 2022)
In eastern boundary current systems, strong coastal upwelling brings deep, nutrient‐rich waters to the surface ocean, supporting a productive food web. The nitrate load in water masses that supply the region can be impacted by a variety of climate‐related processes that subsequently modulate primary productivity. In this study, two coastal upwelling regimes along central and southern California were sampled seasonally for nitrogen and oxygen stable isotopes of nitrate (i.e., nitrate isotopes) over several years (2010–2016) on 14 California Cooperative Oceanic Fisheries Investigations (CalCOFI) cruises. Seasonal, interannual, and spatial variations in euphotic zone nitrate isotopes were largely driven by the extent of nitrate utilization, sometimes linked to iron limitation of diatom productivity. Pronounced isotopic enrichment developed with the El Niño conditions in late 2015 and early 2016 which likely resulted from increased nitrate utilization linked to reduced nitrate supply to the euphotic zone. Differential enrichment of nitrogen and oxygen isotopes was observed in the surface ocean, suggesting that phytoplankton increased their reliance on locally nitrified (recycled) nitrate during warmer and more stratified periods. Overall, nitrate isotopes effectively differentiated important euphotic zone processes such as nitrate assimilation and nitrification, while archiving the influence of disparate controls such as iron limitation and climatic events through their effects on nitrate utilization and isotopic fractionation.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Decomposition of Reaching Movements Enables Detection and Measurement of Ataxia - Brandon Oubre; Jean-Francois Daneault; Kallie Whritenour; Nergis C. Khan; Christopher D. Stephen; Jeremy D. Schmahmann; Sunghoon Ivan Lee; Anoopum S. Gupta (The Cerebellum, 2021)
Technologies that enable frequent, objective, and precise measurement of ataxia severity would benefit clinical trials by lowering participation barriers and improving the ability to measure disease state and change. We hypothesized that analyzing characteristics of sub-second movement profiles obtained during a reaching task would be useful for objectively quantifying motor characteristics of ataxia. Participants with ataxia ( N =88), participants with parkinsonism ( N =44), and healthy controls ( N =34) performed a computer tablet version of the finger-to-nose test while wearing inertial sensors on their wrists. Data features designed to capture signs of ataxia were extracted from participants’ decomposed wrist velocity time-series. A machine learning regression model was trained to estimate overall ataxia severity, as measured by the Brief Ataxia Rating Scale (BARS). Classification models were trained to distinguish between ataxia participants and controls and between ataxia and parkinsonism phenotypes. Movement decomposition revealed expected and novel characteristics of the ataxia phenotype. The distance, speed, duration, morphology, and temporal relationships of decomposed movements exhibited strong relationships with disease severity. The regression model estimated BARS with a root mean square error of 3.6 points, r 2 = 0.69, and moderate-to-excellent reliability. Classification models distinguished between ataxia participants and controls and ataxia and parkinsonism phenotypes with areas under the receiver-operating curve of 0.96 and 0.89, respectively. Movement decomposition captures core features of ataxia and may be useful for objective, precise, and frequent assessment of ataxia in home and clinic environments.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Organic Matter Composition at Ocean Station Papa Affects Its Bioavailability, Bacterioplankton Growth Efficiency and the Responding Taxa - Brandon M. Stephens; Keri Opalk; Daniel Petras; Shuting Liu; Jacqueline Comstock; Lihini I. Aluwihare; Dennis A. Hansell; Craig A. Carlson (Frontiers in Marine Science, 2020)
The bioavailability of organic matter (OM) to marine heterotrophic bacterioplankton is determined by both the chemical composition of OM and the microbial community composition. In the current study, changes in OM bioavailability were identified at Ocean Station Papa as part of the 2018 Export Processes in the Ocean from Remote Sensing (EXPORTS) field study. Removal rates of carbon (C) in controlled experiments were significantly correlated with the initial composition of total hydrolyzable amino acids, and C removal rates were high when the amino acid degradation index suggested a more labile composition. Carbon remineralization rates averaged 0.19 ± 0.08 μmol C L –1 d –1 over 6–10 days while bacterial growth efficiencies averaged 31 ± 7%. Amino acid composition and tandem mass spectrometry analysis of compound classes also revealed transformations to a more degraded OM composition during experiments. There was a log2-fold increase in the relative abundances of 16S rDNA-resolved bacterioplankton taxa in most experiments by members of the Methylophilaceae family (OM43 genus) and KI89A order. Additionally, when OM was more bioavailable, relative abundances increased by at least threefold for the classes Bacteroidetes ( Flavobacteriaceae NS2b genus), Alphaproteobacteria ( Rhodobacteraceae Sulfitobacter genus), and Gammaproteobacteria ( Alteromonadales and Ectothiorhodospiraceae orders). Our data suggest that a diverse group of bacterioplankton was responsible for removing organic carbon and altering the OM composition to a more degraded state. Elevated community diversity, as inferred from the Shannon–Wiener H index, may have contributed to relatively high growth efficiencies by the bacterioplankton. The data presented here shed light on the interconnections between OM bioavailability and key bacterioplankton taxa for the degradation of marine OM.

Forest Vegetation Change and Its Impacts on Soil Water Following 47 Years of Managed Wildfire - Jens T. Stevens; Gabrielle F. S. Boisramé; Ekaterina Rakhmatulina; Sally E. Thompson; Brandon M. Collins; Scott L. Stephens (Ecosystems, 2020)

Landscape-scale drivers of fish faunal homogenization and differentiation in the eastern United States - Brandon K. Peoples; Amy J. S. Davis; Stephen R. Midway; Julian D. Olden; Lauren Stoczynski (Hydrobiologia, 2020)

Morphological Diversification under High Integration in a Hyper Diverse Mammal Clade - Brandon P. Hedrick; Gregory L. Mutumi; V. David Munteanu; Alexa Sadier; Kalina T. J. Davies; Stephen J. Rossiter; Karen E. Sears; Liliana M. Dávalos; Elizabeth Dumont (Journal of Mammalian Evolution, 2020)

An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.

Euphotic zone nitrification in the California Current Ecosystem - Brandon M. Stephens; Scott D. Wankel; J. Michael Beman; Ariel J. Rabines; Andrew E. Allen; Lihini I. Aluwihare (Limnology and Oceanography, 2020)
Nitrification, the microbial conversion of ammonium to nitrite then to nitrate, occurs throughout the oceanic water column, yet the environmental factors influencing the production of nitrate in the euphotic zone (EZ) remain unclear. In this study, the natural abundances of N and O isotopes (δ 15 N and δ 18 O, respectively) in nitrate were used in an existing model framework to quantify nitrate contributed by EZ nitrification in the California Current Ecosystem (CCE) during two anomalously warm years. Model data estimated that between 6% and 36% of the EZ nitrate reservoirs were derived from the combined steps of nitrification within the EZ. The CCE data set found nitrification contributions to EZ nitrate to be positively correlated with nitrite concentrations ( ) at the depth of the primary nitrite maximum (PNM). Building on this correlation, EZ nitrification in the southern California Current was estimated to contribute on average 20% ± 6% to EZ nitrate as inferred using the PNM of the long‐term California Cooperative Oceanic Fisheries Investigation (CalCOFI) survey record. A multiple linear regression analysis of the CalCOFI PNM time series identified two conditions that led to positive deviations in . Enhanced PNM , and potentially enhanced EZ nitrification, may be linked to (1) reduced phytoplankton competition for ammonium ( ) and as interpreted from particulate organic carbon:chlorophyll ratios, and/or (2) to increased supply of (and then oxidation to ) from the degradation of organic nitrogen as interpreted from particulate organic nitrogen concentrations.

High-Resolution Liquid Chromatography Tandem Mass Spectrometry Enables Large Scale Molecular Characterization of Dissolved Organic Matter - Daniel Petras; Irina Koester; Ricardo Da Silva; Brandon M. Stephens; Andreas F. Haas; Craig E. Nelson; Linda W. Kelly; Lihini I. Aluwihare; Pieter C. Dorrestein (Frontiers in Marine Science, 2017)

Managed Wildfire Effects on Forest Resilience and Water in the Sierra Nevada - Gabrielle Boisramé; Sally Thompson; Brandon Collins; Scott Stephens (Ecosystems, 2017)

Incorporating Resource Protection Constraints in an Analysis of Landscape Fuel-Treatment Effectiveness in the Northern Sierra Nevada, CA, USA - Christopher B. Dow; Brandon M. Collins; Scott L. Stephens (Environmental Management, 2016)

Terrestrial and marine perspectives on modeling organic matter degradation pathways - Adrian B. Burd; Serita Frey; Anna Cabre; Takamitsu Ito; Naomi M. Levine; Christian Lønborg; Matthew Long; Marguerite Mauritz; R. Quinn Thomas; Brandon M. Stephens; Tom Vanwalleghem; Ning Zeng (Global Change Biology, 2016)
Organic matter (OM) plays a major role in both terrestrial and oceanic biogeochemical cycles. The amount of carbon stored in these systems is far greater than that of carbon dioxide (CO 2 ) in the atmosphere, and annual fluxes of CO 2 from these pools to the atmosphere exceed those from fossil fuel combustion. Understanding the processes that determine the fate of detrital material is important for predicting the effects that climate change will have on feedbacks to the global carbon cycle. However, Earth System Models (ESMs) typically utilize very simple formulations of processes affecting the mineralization and storage of detrital OM. Recent changes in our view of the nature of this material and the factors controlling its transformation have yet to find their way into models. In this review, we highlight the current understanding of the role and cycling of detrital OM in terrestrial and marine systems and examine how this pool of material is represented in ESMs. We include a discussion of the different mineralization pathways available as organic matter moves from soils, through inland waters to coastal systems and ultimately into open ocean environments. We argue that there is strong commonality between aspects of OM transformation in both terrestrial and marine systems and that our respective scientific communities would benefit from closer collaboration.

Characterisation of major histocompatibility complex class I genes at the fetal-maternal interface of marsupials - Ina Buentjen; Barbara Drews; Stephen R. Frankenberg; Thomas B. Hildebrandt; Marilyn B. Renfree; Brandon R. Menzies (Immunogenetics, 2015)

Evaluation of a Modular System for Low-Cost Transport and Storage of Herbaceous Biomass - Stephen W. Searcy; Brandon E. Hartley; J. Alex Thomasson (BioEnergy Research, 2014)

Mortality of resprouting chaparral shrubs after a fire and during a record drought: physiological mechanisms and demographic consequences - R. Brandon Pratt; Anna L. Jacobsen; Aaron R. Ramirez; Anjel M. Helms; Courtney A. Traugh; Michael F. Tobin; Marcus S. Heffner; Stephen D. Davis (Global Change Biology, 2014)
We examined postfire regeneration of chaparral shrubs during an intense drought. This study focused on the demography and physiology of shrub species that resprout from a basal lignotuber following fire. We found significant levels of resprout mortality when intense drought occurred in the year following fire during the period of shrub recovery. Three of the seven sampled resprouting species had the greatest or near greatest levels of mortality ever recorded when compared to previous studies. Most shrub mortality occurred during the drought after individuals had resprouted (i.e. individuals survived fire, resprouted and then subsequently died). Physiological measurements of species with high mortality suggested that resprout stems were highly embolized and xylem hydraulic conductivities were close to zero during the peak of the drought. In addition, lignotubers of two of the three species experiencing high mortality were depleted of starch. Population densities of most shrub species declined after the drought compared with their prefire levels, with the exception of one drought tolerant obligate seeding species. Resprouting shrub species may deplete their carbohydrate reserves during the resprouting process, making them particularly vulnerable to drought because of the need to transpire water to acquire the CO 2 that is used to supply energy to a large respiring root system. Drought appears to interact with fire by altering postfire shrub recovery and altering species abundances and composition of chaparral communities.

Tolerance to cannabinoid-induced behaviors in mice treated chronically with ethanol - Matthew J. Pava; Emily M. Blake; Stephen T. Green; Brandon J. Mizroch; Patrick J. Mulholland; John J. Woodward (Psychopharmacology, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Simulating Fire and Forest Dynamics for a Landscape Fuel Treatment Project in the Sierra Nevada - Brandon M. Collins; Scott L. Stephens; Gary B. Roller; John J. Battles (Forest Science, 2011)
We evaluated an actual landscape fuel treatment project that was designed by local US Forest Service managers in the northern Sierra Nevada. We modeled the effects of this project on reducing landscape-level fire behavior at multiple time steps, up to nearly 30 years beyond treatment implementation. In addition, we modeled planned treatments under multiple diameter-limited thinning scenarios to assess potential impacts on fuel treatment effectiveness. The planned fuel treatments reduced modeled conditional burn probabilities substantially across the landscape relative to those for a scenario with no simulated treatments. This reduction relative to that for the no treatment landscape was evident approximately 20 years after simulated treatment implementation. Although diameter-limited thinning scenarios resulted in different residual forest stand structures, we detected no real differences in modeled landscape-level burn probabilities. The modeling adaptations we made with respect to fuel model selection and simulated ingrowth/regeneration over simulated time, as well as incorporation of variable winds in fire simulations, collectively contribute to a robust analysis of the study area.

DOM characteristics along the continuum from river to receiving basin: a comparison of freshwater and saline transects - Brandon M. Stephens; Elizabeth C. Minor (Aquatic Sciences, 2010)

Challenges and Approaches in Planning Fuel Treatments across Fire-Excluded Forested Landscapes - Brandon M. Collins; Scott L. Stephens; Jason J. Moghaddas; John Battles (Journal of Forestry, 2010)
Placing fuel reduction treatments across entire landscapes such that impacts associated with high-intensity fire are lessened is a difficult goal to achieve, largely because of the immense area needing treatment. As such, fire scientists and managers have conceptually developed and are refining methodologies for strategic placement of fuel treatments that more efficiently limit the spread and severity of fire across forested landscapes. Although these methodologies undoubtedly improve managers' ability to plan and evaluate various landscape fuel treatment scenarios, there is still a considerable gap between modeling landscape fuel treatments and actually implementing these treatments “on the ground.” In this article we explore this gap in light of decisions managers make with regards to the type, intensity, placement/pattern, and size of fuel treatments. Additionally, we highlight several critical constraints acting on managers when implementing fuel treatments across landscapes and offer some suggestions for dealing with these constraints.

Papyriferic Acid, An Antifeedant Triterpene From Birch Trees, Inhibits Succinate Dehydrogenase From Liver Mitochondria - Stuart McLean; Stephen M. Richards; Siow-Leng Cover; Sue Brandon; Noel W. Davies; John P. Bryant; Thomas P. Clausen (Journal of Chemical Ecology, 2009)

Interactions Among Wildland Fires in a Long-Established Sierra Nevada Natural Fire Area - Brandon M. Collins; Jay D. Miller; Andrea E. Thode; Maggi Kelly; Jan W. van Wagtendonk; Scott L. Stephens (Ecosystems, 2009)

Theoretical modeling of micro-scale biological phenomena in human coronary arteries - Kelvin Wong; Jagannath Mazumdar; Brandon Pincombe; Stephen G. Worthley; Prashanthan Sanders; Derek Abbott (Medical & Biological Engineering & Computing, 2006)

Bileaflet Aortic Valve Prosthesis Pivot Geometry Influences Platelet Secretion and Anionic Phospholipid Exposure - Brandon R. Travis; Ulla M. Marzec; Hwa Liang Leo; Takki Momin; Christine Sanders; Stephen R. Hanson; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2001)